2020
DOI: 10.3390/nu12113564
|View full text |Cite
|
Sign up to set email alerts
|

Meeting of Minds around Food Addiction: Insights from Addiction Medicine, Nutrition, Psychology, and Neurosciences

Abstract: This review, focused on food addiction (FA), considers opinions from specialists with different expertise in addiction medicine, nutrition, health psychology, and behavioral neurosciences. The concept of FA is a recurring issue in the clinical description of abnormal eating. Even though some tools have been developed to diagnose FA, such as the Yale Food Addiction Scale (YFAS) questionnaire, the FA concept is not recognized as an eating disorder (ED) so far and is even not mentioned in the Diagnostic and Stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 148 publications
(238 reference statements)
2
24
0
Order By: Relevance
“…Food addiction may be involved in the pathogenesis of obesity [ 28 ], in fact, some authors suggest that weight loss may also exert an effect on food addiction by decreasing food addiction [ 29 ]. The prevalence of food addiction in obese patients ranges from 16.5% to 40% and may even be higher if the patient also has some other type of eating disorder [ 28 ]. In this study, the prevalence of food addiction among overweight/obese students was 42.4% and, in line with previous studies, relationships between food addiction and BMI were also found.…”
Section: Discussionmentioning
confidence: 99%
“…Food addiction may be involved in the pathogenesis of obesity [ 28 ], in fact, some authors suggest that weight loss may also exert an effect on food addiction by decreasing food addiction [ 29 ]. The prevalence of food addiction in obese patients ranges from 16.5% to 40% and may even be higher if the patient also has some other type of eating disorder [ 28 ]. In this study, the prevalence of food addiction among overweight/obese students was 42.4% and, in line with previous studies, relationships between food addiction and BMI were also found.…”
Section: Discussionmentioning
confidence: 99%
“…A better understanding of the mechanisms underlying the action of cocaine and its links to the reward circuits activated by food intake is essential to address both drug addiction and obesity. In fact, obesity is not only considered an epidemic (see literature 66 for recent review), but it also shares characteristics of drug addiction. Furthermore, the possibility of biased signaling 67–70 combined with targeting dopamine and ghrelin receptor‐containing functional units opens up new avenues for the treatment of addiction and/or eating disorders.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…These seven original studies investigate the factors associated with this phenotype in different contexts: patients seeking treatment for an eating disorder, including anorexia nervosa, bulimia nervosa or binge eating disorder [ 12 , 13 ], patients seeking treatment for obesity (i.e., bariatric surgery candidates) [ 14 ], and non-clinical populations (i.e., persons not directly seeking treatment for these conditions) such as adolescents [ 15 ], female restrained eaters [ 16 ], and persons with weight-related disorders recruited in the general population [ 17 ]. This special issue also present four literature reviews that focus on: neuroimaging of sex/gender differences in obesity, in which FA is prevalent [ 18 ], involvement of the melanocortin system in binge eating, food reward and motivation [ 19 ], association between addictive-like eating behavior and attention-deficit/hyperactivity disorder (ADHD) [ 20 ], and a discussion about the FA concept and its practical implications through four complementary disciplines: addiction medicine, nutrition, health psychology, and behavioral neuroscience [ 21 ].…”
mentioning
confidence: 99%
“…A comprehensive understanding of the factors associated with the addictive-like eating behavior phenotype is a preliminary step towards tailor-based treatments. In a review published in this special issue, Constant et al argues in favor of a multidisciplinary dialogue between specialists in addiction medicine, clinical nutrition, health psychology, and behavioral neuroscience to account for and manage the complexity of FA [ 21 ]. After the presentation of each specialist’s point of view as well as a literature review in each field, they proposed a multidisciplinary framework and practical implications derived from this framework in order to improve FA prevention, diagnosis, and treatment in at-risk populations.…”
mentioning
confidence: 99%